Marcus Simaika : father of coptic archaeology - Simaika, Samir (The American University in Cairo Press, 2018)
Marcus Pasha Simaika (1864-1944) was born to a prominent Coptic family on the eve of the inauguration of the Suez Canal and the British occupation of Egypt. From a young age, he developed a passion for Coptic heritage and devoted his life to shedding light on centuries of Christian Egyptian history that had been neglected by ignorance or otherwise belittled and despised. He was not a professional archaeologist, an excavator, or a specialist scholar of Coptic language and literature